In such
cases, number of zeros equal to number of 9s in (10

^{n}-1) are put extreme right of N to make a new number M and then N is subtracted from this new number to get the result. Clearly, (M - N) is the result of multiplication.
Example-
Multiply 6243 with 999.

Solution.
Here, N=6243, (10

^{n}1)=(10^{3}-1) = 999
According to
the rule,

(N) (M) (N)

6243*999=6243000 - 6243

999
has three 9s and hence

Three zero are put at
the right

End of N to make M.

N is
subtracted from M

To get the
result

Of
multiplication.

Therefore-
(M-N)=6236757

## No comments:

## Post a Comment